PENGEMBANGAN MODEL NASKAH SENI OPERA UNTUK MENGEMBANGKAN PSYCHOSOCIAL PESERTA DIDIK DALAM PEMBELAJARAN IPS KELAS V SD - Adelia Nurhaliza, - (2020)
This research is motivated by the incomplete learning process of social studies which develops the psychosocial skills of elementary school students and the less variative learning model used in facilitating students' psychosocial skills. Psychosocial skills will not be achieved by themselves without efforts and supporting facilities including the learning model used. Therefore, this study aims to identify psychosocial aspects that can be developed through opera art, making opera art scripts to develop psychosocial and validating opera art scripts to develop psychosocial learning in social studies of grade V. This research is a qualitative descriptive study using the D&D Research method (Design and Development Research). Data collection was done using data collection tools, that is validation sheets and judgement instrument sheets. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The results showed that the development of opera art scripts fell into the "Very Good" category. From the validation results carried out by two expert lecturers, art experts and psychosocial competence, opera art script got an average score of 4.8 with a percentage of 98%. That way, the opera art script can be used as one of the social studies learning model that can be applied in schools and facilitates students in understanding and applying psychosocial in daily life. However, teacher creativity is needed in developing opera art scripts that instilled these psychosocial skills so that the results obtained by students are even more optimal.